Protective effects of dietary nutrients on hearing loss: a systematic review and meta-analysis - Lu, Wang; Tang, Rui; Jiahui, Xiong; Shipeng, Zhang; Tao, Guo; Hanyua, Wang; Feng, Xiong; Hui, Xie (Frontiers in Nutrition, 2025)
BackgroundHearing loss ranks as the third most prevalent disability globally, significantly impacting individuals and society, and imposing a substantial healthcare burden. The World Health Organization reports that over 1.5 billion people worldwide experience hearing loss, with one-third of these cases attributed to preventable factors. Recently, the influence of diet and nutrition on auditory health has garnered increasing attention.ObjectiveThis study systematically reviews and meta-analyzes the protective effects of dietary nutrients on hearing, examining specific nutrients' impact on hearing loss and their potential biological mechanisms.MethodsA comprehensive search of PubMed, Embase, Web of Science, and the Cochrane Library was conducted for relevant studies up to August 2024. Following PRISMA guidelines, the systematic review was registered in PROSPERO. Included were observational studies assessing the relationship between dietary intake and hearing loss.ResultsThirty-three studies met inclusion criteria: 21 cross-sectional, 10 cohort, and 2 case-control studies. Meta-analysis revealed significant inverse associations between the intake of vitamin B2, β-carotene, carotenoids, β-cryptoxanthin, fat, protein, fiber, and fish, and the risk of hearing loss.ConclusionCertain dietary nutrients may protect hearing health. Increasing intake of antioxidants, fiber, protein, and fish rich in unsaturated fatty acids may help preserve auditory function.Keywords: Hearing loss, dietary nutrients, systematic review, meta-analysis, antioxidants.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024572118, identifier: CRD42024572118.